Anomalous oscillatory features in neutron emission from D + D fusion in palladium at 100 keV implantation energy. (22nd May 2019) - Choudhury, R. K.; Kumar, Ajay; Thomas, R. G.; Mishra, G.; Mitra, A.; Nayak, B. K.; Saxena, A.
Abstract: Neutron yield in D + D fusion in a palladium foil, kept at about temperature, has been measured as a function of the number of implanted ions at a bombarding energy of 100 keV. A considerably large oscillatory pattern was observed riding on a systematic increment for the emitted neutron yield as a function of the number of implanted ions. Such an oscillatory behaviour is in contrast with the expected neutron yield calculated using the bare D + D fusion cross-section. The present observation seems to indicate that the bare cross-section is significantly affected due to the lattice effects of the host metal at large atomic ratios.